Índice de potencial turístico da região geográfica imediata de Princesa Isabel, no semiárido paraibano - Albuquerque, Erickson Melo de (2022)
Tourism in this research is seen as a multidimensional-systemic-spatial phenomenon, which reaches beyond the economy. It is, above all, a social phenomenon, carried out by people, that re-signifies territories and (re)produces spaces. In accordance with the hegemonic capitalist economic model in the world, it is guided by the consumption of places, for which the landscape is seen as a commodity. In this sense, tourism and its various segments concentrate efforts to attract the masses, as a way of feeding the logic of accumulation, while creating employment and income, albeit in a socially unequal way. The large urban centers and surrounding localities have historically benefited from the processes of construction of tourist spaces to consolidate them, but the tourist potential does not depend on financial investments to exist, although this is an important driver, since the potential - that is, what it can be - resides in the possibility of taking advantage of the landscapes, resulting from historically accumulated relationships between society, nature and between both, for the offer of leisure. Therefore, in the most distant locations from these large centers, there are greater difficulties to develop tourism as an alternative to diversify the economy, strengthen social processes and conserve the environment, especially due to the indetermination of the existing potential. With the objective of evaluating the tourist potential of the Immediate Geographical Region of Princesa Isabel - RGIPI, composed by five municipalities in the Sertão of Paraíba state, through the elaboration of a multidimensional index, assured by the use of geotechnologies, this research starts from the hypotheses that the elaboration of a multidimensional index to evaluate the tourist potential makes it possible to identify territorial weaknesses and potential for the development of tourism; and that there is a tourist potential capable of promoting territorial development in the region. For this, indicators were used to measure the socioeconomic, environmental, spatial, legal, political and administrative aspects, and the tourist structure, such as attractions, support infrastructure and tourist services and equipment. The elaboration of tourist cartography resulting from the support of geotechnology, materializes in unpublished tourist maps about the region, making it possible to provide tourist planning. Then, the indicators had their scales normalized, were integrated to form the Tourism Potential Index - IPT of RGIPI, and subsidized an interrelated analysis between the elements. The results showed that the municipality of Princesa Isabel confirmed itself as a regional tourist hub, holding the best-rated tourist heritage in the region, accompanied by Manaíra, São José de Princesa, Juru, and Tavares. A variety of tourist segments with potential to be developed were identified (historical, religious, ecotourism, geotourism, gastronomic, among others), favored by the spatial arrangement of potentially tourist spots, although the support infrastructure, tourist services and equipment, the conditions socioeconomic and environmental issues are important weaknesses. Finally, it is considered that the IPT fulfilled its function by providing a measure of the performance of the components and the tourism system, enabling an analysis of the behavior of the phenomenon and producing knowledge to support the planning and management of tourism in the region.